An Analysis Patient Safety Goals in Aspect Implementation Identification and Treatment Medicines in the Inpatient Room of the Tenriawaru Hospital Bone Regency - Dewi Mulfiyanti; Nunik Sulistyaningtyas; Rismayanti Yamin (International Journal of Public Health Excellence (IJPHE), 2022)
House sick have obligation for give service in accordance with right patient and safety patient. Accuracy identification patient and storage drug (high alerts) is part from patient safety. In Tenriawaru General Hospital Bone Regency still there is patient which no identified with Correct and still there is drugs (high alerts levels) which no permanent in accordance SOUP. Destination from study this is for knowing implementation identification patient and security drug (high alerts) in Tenriawaru General Hospital Bone Regency with theory system. Method study this is descriptive qualitative and use tool study form guidelines Interview and sheet observation. Interview conducted with Director HOSPITAL Tenriawaru Bone Regency, Secretary Committee quality, Nurse executor and Staff Safety patient . Results study show that identification patient and application security drug (high alerts) permanent walk, however not yet fully in accordance with regulation PMK 1691/MENKES/PER/VII/2011. Thing this caused by source power man which no sufficient, lack of training head room , Disobedient to instructions SOUP which has determined , noncommitment head room, and lateness delivery report safety patient to KMKP. Suggestion from study this is Activation officer TKPRS in ward house sick , maintenance training routine , monitoring obedience to SOUP related identification patient and monitoring security drug through videos surveillance and questionnaire patient for evaluation nurse, and waiver inspection patient must improved. Recording and reporting Culture case patient.